Pendidikan Pengetahuan Tentang Gizi dan Kesehatan Gigi & Mulut pada Orang Tua Murid TK Aisyiah Joyosuran, Surakarta - Widia Susanti; Risya Cilmiaty A.R; Betty Saptiwi; Adi Prayitno; Alfiyah Pujiyati; Meirina Mulia Wardani; Filumena T. R; Norma Mukti Bimacahya; Satria Wardana; Afrizal Tri Heryadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Aisyiyah Joyosuran Kindergarten is one of the kindergartens located on Jl. Cikarang No.22, Gabudan RT 01 RW 08 Joyosuran, Pasar Kliwon District, Surakarta City, Central Java. Children can grow up to be healthy and smart through the process of growth and development. Nutrition has the most important effect on growth. Based on Riskesdas data (2018), the proportion of daily tooth brushing behavior of people aged three years and over is 94.7%, but the proportion who brush their teeth properly is only 2.8%. This is a problem because one of the effective prevention methods against the occurrence of dental and oral disease is through the act of brushing teeth. The purpose of this service is to carry out the Community Service component of the Tri Dharma of Higher Education. The benefit of this service is to increase knowledge education about nutrition and dental & oral health for parents of Aisyiyah Joyosuran Kindergarten students, Surakarta. The service method is lectures and training on knowledge about nutrition and dental & oral health. The target audience was 84 parents of Aisyiah Joyosuran Kindergarten students. The results of the service show that the activities run smoothly. Participants are expected to be able to provide education about good nutrition and dental & oral health to their children while providing nutrition according to the RDA according to the Ministry of Health and maintenance of dental and oral health.